Comparison of patients’ and nurses’ viewpoints about responsiveness among a sample from public and private hospitals of Isfahan - Javadi, Marzieh (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Health systems search for ways of making their services more responsive to patients and the public The new framework of the World Health Organization (WHO) for assessment of health system performance has determined health, responsiveness and fairness of financing as the main goals. This study aimed to compare patients’ and nurses’ view points about responsiveness among a sample of public and private hospitals of Isfahan, Iran. METHODS: A descriptive study was conducted on 160 nurses and also equal number of patients. Data were collected by a valid and reliable questionnaire designed by WHO. Data were analyzed using SPSS software. Scores were reported as mean (standard deviation). RESULTS: Mean score of responsiveness was 2.4(0.58) in nurses and 2.3(0.54) in patients but the difference was not statistically significant (out of a maximum of 4). The corresponding figures were significantly different (p = 0.009) regarding patients’ viewpoints in public [2.2(0.4)] and private hospitals [2.3(0.5)]. CONCLUSIONS: Proper satisfaction about responsiveness was not provided in studied hospitals, based on the nurses’ and patients’ points of view. Public hospitals, in spite of their high costs, had a worse situation about responsiveness; the improvement of this situation necessitates managerial policies.